2018
DOI: 10.1038/s41429-018-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide and phenolic metabolites from the marine-derived fungus Paraconiothyrium sp. VK-13 with anti-inflammatory activity

Abstract: Five new secondary metabolites, modiolides D-G (1-4) and 1-(2,5-dihydroxyphenyl)-3-methoxy-butan-1-one (8), one new natural product, 1-(2,5-dihydroxyphenyl)-3-hydroxybutan-1-one (7), along with three known compounds, modiolides A (5) and B (6), and 1-(2,5-dihydroxyphenyl)-2-buten-1-one (9) were isolated from a fermentation culture of the marine endophytic fungus Paraconiothyrium sp. VK-13. Their chemical structures were elucidated by the NMR and MS spectroscopic analysis as well as the modified Mosher's method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Further analysis revealed that these compounds significantly induce the suppression of iNOS and COX-2 protein expression. Furthermore, both compounds inhibited the mRNA expression of TNF-α, IL-1β, IL-6, and IL-12, with IC 50 values ranging from 2.4-12.5 µM [127]. Similarly, chaetoglobosin Fex (158), a compound isolated from marine-derived endophytic fungus Chaetomium globosum QEN-14 was also reported to significantly inhibit the production of TNF-α, IL-6 and monocyte chemotactic protein-1 (MCP-1) in peritoneal macrophages and murine macrophage cell line RAW264.7.…”
Section: Anti-inflammatory Metabolites Produced By Endophytic Fungi Fmentioning
confidence: 98%
“…Further analysis revealed that these compounds significantly induce the suppression of iNOS and COX-2 protein expression. Furthermore, both compounds inhibited the mRNA expression of TNF-α, IL-1β, IL-6, and IL-12, with IC 50 values ranging from 2.4-12.5 µM [127]. Similarly, chaetoglobosin Fex (158), a compound isolated from marine-derived endophytic fungus Chaetomium globosum QEN-14 was also reported to significantly inhibit the production of TNF-α, IL-6 and monocyte chemotactic protein-1 (MCP-1) in peritoneal macrophages and murine macrophage cell line RAW264.7.…”
Section: Anti-inflammatory Metabolites Produced By Endophytic Fungi Fmentioning
confidence: 98%
“…One new phenolic metabolite, 1-(2,5-dihydroxyphenyl)-3-hydroxybutan-1-one (105, Figure 18), along with 1-(2,5-dihydroxyphenyl)-2-buten-1-one (106, Figure 18), were found in the EtOAc extract of the marine endophytic fungus Paraconiothyrium sp. VK-13 [61]. 1-(2,5-dihydroxyphenyl)-3- hydroxybutan-1-one and 1-(2,5-dihydroxyphenyl)-2-buten-1-one displayed inhibitory effect against iNOS derived NO and COX-2 derived PGE 2 in LPS-stimulated RAW264.7 cells, with IC 50 values from 3.9 and 12.5 µM [61].…”
Section: Polyketidesmentioning
confidence: 99%
“…1-(2,5-dihydroxyphenyl)-3- hydroxybutan-1-one and 1-(2,5-dihydroxyphenyl)-2-buten-1-one displayed inhibitory effect against iNOS derived NO and COX-2 derived PGE 2 in LPS-stimulated RAW264.7 cells, with IC 50 values from 3.9 and 12.5 µM [61]. The anti-inflammatory effects of these compounds were attributed to the significant inhibition of the expression of iNOS and COX-2 proteins and the inhibition of mRNA expression of anti-pressure cytokines including TNF- α , IL-1 β , IL-6, and IL-12 [61]. From a marine crinoid collected in Xuwen, Zhanjing City, Guangdong Province, China, fungal strain Leptosphaerulina chartarum 3608, was selected for chemical study [62].…”
Section: Polyketidesmentioning
confidence: 99%
“…[7] However, chemical profile of the Xenomyrothecium genus has yet to be discovered so far. In our continuing search for secondary metabolites from the Vietnamese marinederived fungi, [8,9] we conducted a chemical investigation of a fungal strain Xenomyrothecium sp. IMBC-FP2.11 isolated from an unidentified sponge.…”
Section: Introductionmentioning
confidence: 99%